Reliability Assessment of Bangla Version of the Shoulder Pain and Disability Index (SPADI) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not availableJ Bangladesh Coll Phys Surg 2022; 40: 145